KAJIAN MAKNA PADA FOTO KARYA ANTON ISMAEL RESEARCH STUDI OF MEANING ON PHOTOS BY MR. ANTON ISMAEL - Candra Prayogi; Agung Eko Budiwaspada; Yan Yan Sunarya (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2019)
AbstractThis research aims to describe Anton Ismael's photography works seen from the study of semiotics. The research subject was a photographic work related to social issues around an attractive environment by Anton Ismael. While the object of research is in the form of material objects and formal objects (objects that are invisible, which are in the work of Anton Ismael which can be studied using semiotics). The research focused on the problems related to Anton Ismael's photographic works seen from the study of semiotics Charles Sander Peirce and Roland Barthes. The results of the study show that: (1) Anton Ismael's photographic works are based on Charles Sanders Peirce's theories such as icons, indices and symbols. The iconic forms in the work include high school students, high school uniforms, roses, mountains, places to eat, instant noodles and others. The index on photo works contains the life of school children, problems that often arise in school, school environment. (2) Analysis of Anton Ismael's photo works seen from the study of semiotics. From the analysis that has been done, in Anton Ismael's photo work always shows the existence of a relationship or relationship between signs. Icons, indexes, and symbols are good in form, print collage, paint and are always related and explain more or less the meaning contained in each work. In other words, photos can describe the contents implied in each work so that the information delivered will be more easily captured. AbstrakPenelitian ini bertujuan untuk mendeskripsikan karya-karya fotografi Anton Ismael dilihat dari kajian semiotika. Subjek penelitian adalah karya foto yang berhubungan dengan isu sosial di sekitar lingkungan yang menarik oleh Anton Ismael. Sedangkan objek penelitian adalah berupa objek material dan objek formal (objek yang tidak kasat mata, yang ada di dalam karya Anton Ismael yang dapat dikaji menggunakan semiotika). Penelitian difokuskan pada permasalahan yang berkaitan dengan karya-karya foto Anton Ismael dilihat dari kajian semiotika Charles Sander Peirce dan Roland Barthes. Hasil penelitian menunjukkan bahwa: (1) karya-karya foto Anton Ismael berdasarkan teori Charles Sanders Peirce seperti, ikon, indeks, dan symbol. Bentuk Ikon dalam karya antara lain berupa siswa-siswi SMA, Seragam SMA, Mawar, Gunung, Tempat makan, Mie Instan dan lain-lain. Indeks pada karya foto berisi tentang kehidupan anak sekolah, permasalahan yang sering timbul di sekolah, lingkungan sekolah., (2) Analisis karya-karya foto Anton Ismael dilihat dari kajian semiotika. Dari analisis yang telah dilakukan, dalam karya foto Anton Ismael selalu menunjukan adanya hubungan atau relasi antar tanda. Ikon, indeks, dan symbol baik pada bentuk, kolase print, cat dan selalu berkaitan dan sedikit banyak menjelaskan makna yang terkandung dalam setiap karya. Dengan kata lain, foto dapat menggambarkan isi yang tersirat di dalam setiap karya sehingga informasi yang disampaikan akan lebih mudah ditangkap.